2007
DOI: 10.1139/b07-016
|View full text |Cite
|
Sign up to set email alerts
|

Virulence of, and interactions among, mountain pine beetle associated blue-stain fungi on two pine species and their hybrids in Alberta

Abstract: Mountain pine beetle (MPB) is the most serious pest of lodgepole pine in western Canada, and it is predicted to spread into boreal jack pine within the next few years. Colonization of host trees by MPB-associated blue-stain fungi appears to be required for successful beetle reproduction. Three species of blue-stain fungi, Grosmannia clavigera (Robinson-Jeffery and Davidson) Zipfel, de Beer, and Wingfield (≡ Ophiostoma clavigerum (Robinson-Jeffery and Davidson) Harrington), Ophiostoma montium (Rumbold) von Arx,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 27 publications
3
57
3
Order By: Relevance
“…Studies employing low numbers of inoculations to living trees have been used to assess the length of lesions that result from fungal colonization of the phloem. Under the tree killing hypothesis, lesion length is used as a proxy for virulence and longer lesions are assumed to be produced by more virulent associates (64,65,80,82). In this context, lesion length is used to assess the relative value of each fungus to the bark beetle.…”
Section: The Classic Paradigmmentioning
confidence: 99%
“…Studies employing low numbers of inoculations to living trees have been used to assess the length of lesions that result from fungal colonization of the phloem. Under the tree killing hypothesis, lesion length is used as a proxy for virulence and longer lesions are assumed to be produced by more virulent associates (64,65,80,82). In this context, lesion length is used to assess the relative value of each fungus to the bark beetle.…”
Section: The Classic Paradigmmentioning
confidence: 99%
“…Christiansen 1985, Solheim et al 1993, Yamaoka et al 1995, Krokene and Solheim 1998, Kirisits 1998. The lesion length caused by the fungal infestation has been used as a measure to study the virulence of a fungus (Matsuya et al 2003, Rice et al 2007. Under the tree killing hypothesis, the most virulent fungal associates are believed to be the most effective in killing the tree, and therefore the most useful for bark beetles (Yamaoka et al 1990, Solheim andSafranyik 1997).…”
Section: Fungal-host Tree-bark Beetle Interactionsmentioning
confidence: 99%
“…Another hypothesis is that interspecific competition between the fungal associates based on fungal virulence to pine is a mechanism that may explain the differences in the abundance of the fungal associates; G. clavigera was found to be more virulent on lodgepole pine and lodgepole pine × jack pine hybrids than O. montium but there was no difference between the two fungi on jack pine (Rice et al 2007a). A second inoculation study that included all three ophiostomatalean fungi found comparable virulence between all fungi and that lodgepole pine was less susceptible to the fungi than the hybrids with jack pine and pure jack pine, as assessed by lesion length (Rice et al 2007b).…”
Section: Native Insect-fungus Symbiosesmentioning
confidence: 90%